A COMPREHENSIVE REVIEW ON AGRICULTURE AND FARMERS EXPECTATIONS - Mahesh Singh , Girish Garg (International Journal of Modern Agriculture, 2021)
Plant and livestock farming is the study, craft, and practice of agriculture. Agriculture was cornerstone to the rise of sedentary civilization of human, as domesticated species farming produced food surpluses that allowed persons to living in cities. Since India is an agrarian economy, agriculture area employments more than 51% of the total workers in India and contribute about 18 percent to the country’s GDP so there is important to meet the expectations of famer too so that they contribute to increases the GDP country. This paper focuses on agriculture like definition of agriculture, important of agriculture, agriculture biodiversity etc. This paper also focuses on issue that faces by the farmer and solution to overcome these issue. By bridging the divide between minor and significant enterprises, smart farming is predicted to have a massive effect on the agricultural economy in the future. The pattern isn't only relevant in established countries; emerging countries have too understood its significance.